Growth monitoring and promotion service utilization and its associated factors among mothers of children under two years in Ethiopia: a systematic review and meta-analysis - Yilkal Simachew; Arsema Abebe; Amanuel Yoseph; Berhan Tsegaye; Gedion Asnake; Hawa Hassen Ali; Rekiku Fikre (BMC, 2024)
Abstract Background Growth monitoring and promotion (GMP) is a nutritional intervention designed to identify and address growth faltering before a child's nutritional status deteriorates into severe malnutrition. Despite GMP being recognized as a priority in Ethiopia's national nutrition program, there is no national aggregated figure to show the extent of GMP service utilization. Therefore, this systematic review and meta-analysis aimed to assess GMP service utilization and associated factors in Ethiopia. Methods A systematic literature search was conducted using PubMed/MEDLINE, CINAHL, Hinari, EMBASE, Scopus, and grey literature sources like Google Scholar, WorldCat, and Institutional repository. The Joanna Briggs Institution (JBI) quality assessment tool was used to appraise the quality of the articles, and articles scoring > 50% were included in the analysis. The pooled prevalence and odds ratio of associated factors with 95%CI was computed using STATA version 16. A random-effect model was employed to estimate the effect size, and I-squared statistics and Egger's test were used to assess heterogeneity and identify potential publication bias, respectively. Subgroup analysis was conducted with publication year, sample size, and region to identify the source of heterogeneity. Results Nine studies with 4,768 study participants were included in this meta-analysis. The overall pooled utilization of GMP service among children under two years of age in Ethiopia was 23.21% (95% CI: 16.02, 30.41, I2 = 97.27% & P = 0.0001). Mothers who received counselling on GMP service (OR = 3.16 (95%CI: 2.49-4.00), parents who use family health card (FHC) (OR = 3.29 (95%CI: 1.49-7.28), and mother who use postnatal care (OR = 3.93 (95%CI: 2.40-6.42), and Anti natal care (OR = 3.15 (95%CI: 1.29-7.69) were the factors associated with GMP service utilization among children under two years of age. Conclusions The utilization of GMP services among children under the age of two in Ethiopia remains inadequate. Therefore, it is crucial to provide health education and counselling focusing on GMP to the mothers/caregivers of the child and encourage utilization of FHC. In addition, integrating GMP with other maternal health services should be promoted.